Magnetically Actuated Reconfigurable Metamaterials as Conformal Electromagnetic Filters. (7th July 2022) - Wu, Shuai; Eichenberger, Jack; Dai, Jize; Chang, Yilong; Ghalichechian, Nima; Zhao, Ruike Renee
Abstract : Electromagnetic (EM) metamaterials with tailored properties are developed for wave manipulation, filtering, and cloaking for aerospace and defense applications. While traditional EM metamaterials exhibit fixed behaviors due to unchangeable material properties and geometries after fabrication, reconfigurable EM metamaterials allow for tunable performance through electrical/mechanical reconfiguration strategies. Traditional biasing circuit‐based electrical reconfiguration poses challenges due to complex circuit design, while motor‐driven mechanical reconfiguration can lead to bulky and tethered structures with restricted adaptability. Herein, magnetically actuated structurally reconfigurable EM metamaterials with enhanced adaptability/conformability to different geometries, showing merits of fast, reversible, and programmable shape morphing, are developed. Magnetic actuation enables metamaterial's mechanical reconfiguration between flat deployed, flat folded, curved deployed, and curved folded states for both conformal and freestanding 3D shape morphing. Locally, the EM metamaterials fold subwavelength units for tunable properties, switching between all‐pass and band‐stop behaviors upon structural reconfiguration. Globally, the structure can conform and morph to different curved surfaces. The structurally reconfigurable metamaterial also serves as a medium for customizable subwavelength units by rationally designing attached conductive patterns for varied filtering performances such as narrow‐band, dual‐band, and wide‐band filtering behaviors, illustrating the design flexibility and application versatility of the developed structurally reconfigurable EM metamaterial. Abstract : Structurally reconfigurable electromagnetic metamaterials are developed based on magnetically responsive lattices. The structures demonstrate programmable shape morphing between flat deployed, flat folded, curved deployed, and curved folded states upon magnetic actuation. With attached customizable subwavelength units, electromagnetic metamaterials are demonstrated to switch between accepting and rejecting an incident wave by structural reconfiguration.